THE PROBLEM OF TRAINING FUTURE SPECIALISTS TO SAFE LIFE AND ACTIVITY UNDER THE NEW CONDITIONS - Гвоздій, С. П. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article highlights the problem of acquirement modern specialists concerning teaching safety issues of new regulatory rights. It is substantiated the necessity of life safety subjects in the training of future professionals in higher education. It was investigated the state of teaching safety issues at universities around the world, where life safety issue has received considerable attention. The training in these universities of life safety in everyday life, during the occupational safety and emergencies, is conducted gradually. There are suggested ways of mainstreaming and the promotion of safety disciplines in higher educational institutions of Ukraine with the help of a training seminar by means of competitively-tiered training and practical training approaches. It is proved the efficiency of these trainings. The Emphasis is done on the necessity to change the approach of teaching safety with innovative, interactive approaches, as close as possible to the demands of up-to-dateness and the needs of society